The role of intercultural communication in study foreign languages - Feruza Sharipova (Proceedings of The ICECRS, 2019)
Language & Intercultural Communication will promote an understanding of the relationship between language and intercultural communication. It welcomes research into intercultural communication, particularly where it explores the importance of linguistic aspects; and research into language, especially the learning of foreign languages, where it explores the importance of intercultural dimensions.